2021
DOI: 10.1111/adb.13013
|View full text |Cite
|
Sign up to set email alerts
|

Akt and its phosphorylation in nucleus accumbens mediate heroin‐seeking behavior induced by cues in rats

Abstract: Akt is initially identified as one of the downstream targets of phosphatidylinositol‐3 kinase (PI3K) and is involved in morphine reward and tolerance. However, whether phospholyration of Akt (p‐Akt) mediates heroin relapse remains unclear. Here, we aimed to explore the role of p‐Akt in the nucleus accumbens (NAc) in cue‐induced heroin‐seeking behaviors after withdrawal. First, rats were trained to self‐administer heroin for 14 days, after which we assessed heroin‐seeking behaviors induced by a context cue (CC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Dopamine receptor D2 functions through the Akt/GSK-3β signaling cascade (Rosen et al, 2016 ; Wang et al, 2019 ). The present results showed upregulation of the Akt/mTOR/GSK-3β pathway, which is consistent with the previous reports (Zhu et al, 2021 ). Ketamine self-administration decreased the expression of GSK-3β in the NAc (Huang et al, 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…Dopamine receptor D2 functions through the Akt/GSK-3β signaling cascade (Rosen et al, 2016 ; Wang et al, 2019 ). The present results showed upregulation of the Akt/mTOR/GSK-3β pathway, which is consistent with the previous reports (Zhu et al, 2021 ). Ketamine self-administration decreased the expression of GSK-3β in the NAc (Huang et al, 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…Some studies indicated that the PI3K/Akt signaling pathway played an essential role in neuronal survival ( Dudek et al, 1997 ) and neurodegeneration ( Wu et al, 2010 ; Chen et al, 2012 ). Qiao et al reported that drugs (e.g., alcohol, heroin, morphine, and METH) could activate the PI3K/Akt signaling pathway in the cortex, and contribute to addiction ( Qiao et al, 2018 ; Li et al, 2020 ; Meng et al, 2020 ; Zhu et al, 2021 ). The Akt phosphorylation in the NAc was related to heroin-seeking behavior ( Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qiao et al reported that drugs (e.g., alcohol, heroin, morphine, and METH) could activate the PI3K/Akt signaling pathway in the cortex, and contribute to addiction ( Qiao et al, 2018 ; Li et al, 2020 ; Meng et al, 2020 ; Zhu et al, 2021 ). The Akt phosphorylation in the NAc was related to heroin-seeking behavior ( Zhu et al, 2021 ). Furthermore, we detected that the PI3K and Akt mRNA levels in BV2 cells treated with METH and heroin significantly increased than those of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reorganized dopamine hypothesis of psychosis [ 122 ], antipsychotics that block D2Rs were thought to simply reverse striatal hyperdopaminergic activity. So, the antipsychotic drug should simultaneously activate and inhibit dopamine signalling according to the brain region [ 197 ]. Antipsychotic medication might benefit from the discovery that D2Rs are capable of signaling not just through standard G protein pathways but also through noncanonical pathways that induce the creation of a signaling complex involving protein phosphatase2 (PP2A), GSK3 β , 5AKT, and β arr2.…”
Section: Treatment Of Psychiatric Disordersmentioning
confidence: 99%